PENGARUH INFLASI TERHADAP VELOCITY OF MONEY DI INDONESIA - Dian Lubianti (Jurnal Ekonomi Pembangunan, 2005)
The purpose of this research is to find out the effect on the inflation for velocity of money in Indonesian. The sampling period is from 1990 until 2004. Quantitative for analisys are with regression models. The result on regression models is significant to predicable inflation influence on the velocity of money. In this paper, the writer use the Quantity Theory. The writer hope this paper can became the resources of information that can explain in the influence of inflation to velocity of money.Keywords : Inflation, Velocity of Money